2012
DOI: 10.1177/0009922812439243
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Baseline Understanding and Expectations of Antibiotic Use for Their Children

Abstract: Although there is evidence that oral antibiotic prescriptions for children have decreased since the 1990s, antibiotic resistance continues to be a problem. This study evaluated the caregivers' understanding of antibiotic use for their children and identified demographic characteristics that may contribute to inappropriate antibiotic-seeking behavior. Caregivers were asked how often the child should receive antibiotics for common medical conditions and about factors to improve patient compliance. This study fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Eleven studies identified that in private healthcare systems, regular follow‐ups with clinicians either by phone or home/office visit were more common. Parents reported more satisfaction when they knew and trusted their clinician and felt the clinician knew their family (Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Cabral et al., ; Chinnasami et al., ; Ecker et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Zyoud et al., ). However, in three of the studies, parents felt that the clinician did not know their child or discuss their child's health with them, resulting in a feeling of lack of trust in the clinician and reduced compliance from parents (Alkhaldi et al., , Dwibedi et al., ; Wun et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies identified that in private healthcare systems, regular follow‐ups with clinicians either by phone or home/office visit were more common. Parents reported more satisfaction when they knew and trusted their clinician and felt the clinician knew their family (Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Cabral et al., ; Chinnasami et al., ; Ecker et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Zyoud et al., ). However, in three of the studies, parents felt that the clinician did not know their child or discuss their child's health with them, resulting in a feeling of lack of trust in the clinician and reduced compliance from parents (Alkhaldi et al., , Dwibedi et al., ; Wun et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…A dominant theme, identified in the majority of the studies, was the variation in parental knowledge, attitudes and practices on antibiotic use and misuse in children with upper respiratory tract infections (URTIs) (Agarwal et al., ; Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Chan & Tang, ; Chinnasami et al., ; Ecker et al., ; Farha, Suyagh, Alsakran, Alsous, & Alefishat, ; Finkelstein et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Wun et al., ; Yu et al., ; Zyoud et al., ). In fifteen studies, the levels of education were cited as significant to parents' knowledge (Agarwal et al., ; Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Chan & Tang, ; Chinnasami et al., ; Dwibedi et al., ; Ecker et al., ; Farha et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Salonga, ; Vaz et al., ; Yu et al., ). In four studies (Agarwal et al., ; Al‐Dossari, ; Ecker et al., ; Zyoud et al., ), parents could not generally identify or name an antibiotic and only two studies cited that parents had knowledge of the importance of completing antibiotic courses (Agarwal et al., ; Ecker et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When studies collected the data across multiple years, the middle of the date range was used for our analysis. In one study, the year of data collection was not specified . The year was determined as 2006, after communication with the authors …”
Section: Inclusion Criteria and Exclusion Criteriamentioning
confidence: 99%
“…The expectations and behaviors of parents can heavily influence physicians’ attitudes concerning antibiotic prescription [10,18], leading to antibiotic overuse in private practice and PEDs, whereas poor physician-patient rapport in primary care is associated with failure to fill prescriptions [19]. Good understanding of the treatment by the parents may significantly improve treatment adherence [18-22]. Greater parent satisfaction with pediatric care correlated with improved quality of care in the child via better comprehension of medical information and increased treatment adherence [21,23-25].…”
Section: Introductionmentioning
confidence: 99%